Factors that Affect Audit Delay in Companies at LQ 45 - Yulianti, Yulianti; Astutik, Dwi Tri; Widowati, Sri Yuni; Prapti, Lulus (Universitas Negeri Semarang, 2021)
This study aims to examine the effect of total assets, return on assets (ROA), debt to asset ratio (DAR), and auditor’s opinion on audit delay. The population used in this study is LQ 45 companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The number of samples used is 25 companies. The sampling method in this research is purposive sampling. Based on the predetermined sample criteria, the total sample of this research is 100 companies. The type of data used is secondary taken from the company’s financial statements. The analysis technique used in this research is multiple linear regression. The results of the analysis in this study indicate that total assets, return on assets (ROA), debt to asset ratio (DAR) affect audit delay. Audi delay is getting smaller when the company receives pressure from stakeholders. Large companies and those with debt will receive more attention from stakeholders. When profits make the company want to publish its financial statements to related parties immediately. The auditor will remain professional in running the business so that there is no impact from the opinion given by the audit delay. Keywords: Audit Delay; Total Assets; Return on Assets (ROA); Debt to Asset Ratio (DAR); Auditor’s Opinion